2019
DOI: 10.1016/j.jses.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis can predict opioid usage and dependence in reverse shoulder arthroplasty

Abstract: Introduction: Reverse shoulder arthroplasty (RSA) has seen exponential growth over the past 2 decades. In addition, the recent focus on opioid usage and dependence has led to an increased understanding of the risk factors that lead to dependence. The purpose of this study was to examine associations between diagnosis and opioid consumption and dependence in RSA. Methods: A retrospective review was performed of 441 patients who had undergone a primary RSA from 2012 to 2016. Demographics were collected and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The majority of studies in opioid consumption in the shoulder and elbow literature address opioid usage after shoulder procedures, primarily shoulder arthroplasty and rotator cuff repair. [16][17][18][19][20][21][22] One previous study examined risk factors for chronic opioid use after elbow arthroscopy. 23 In this study, Rojas et al using data from a national database found that preoperative opioid filling, fibromyalgia, and psychiatric illness were associated with an increased risk of prolonged postoperative opioid use after elbow arthroscopy, whereas patients <40 years of age and chronic obstructive pulmonary disease were associated with a decreased risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies in opioid consumption in the shoulder and elbow literature address opioid usage after shoulder procedures, primarily shoulder arthroplasty and rotator cuff repair. [16][17][18][19][20][21][22] One previous study examined risk factors for chronic opioid use after elbow arthroscopy. 23 In this study, Rojas et al using data from a national database found that preoperative opioid filling, fibromyalgia, and psychiatric illness were associated with an increased risk of prolonged postoperative opioid use after elbow arthroscopy, whereas patients <40 years of age and chronic obstructive pulmonary disease were associated with a decreased risk.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies in opioid consumption in the shoulder and elbow literature address opioid usage after shoulder procedures, primarily shoulder arthroplasty and rotator cuff repair. 16 , 17 , 18 , 19 , 20 , 21 , 22 One previous study examined risk factors for chronic opioid use after elbow arthroscopy. 23 In this study, Rojas et al.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 32 , 45 , 52 , 61 In the present literature, considerable evidence suggests that preoperative opioid consumption, abuse, or dependence is predictive of increased opioid consumption, prolonged use, and dependence perioperatively and postoperatively ( Table I ). 4 , 13 , 14 , 19 , 39 , 41 , 42 , 43 , 47 , 50 , 52 , 56 , 68 Preoperative opioid use has also been linked to worse clinical outcomes and lower rates of patient satisfaction. 12 , 49 , 63 Sabesan et al found that, compared to other pathologies, use of a reverse shoulder arthroplasty after a proximal humerus fracture was associated with an increased postoperative opioid dependence, and Jildeh et al found specific surgical factors including presence of biceps tenodesis and number of concomitant procedures significantly increased postoperative opioid demand.…”
mentioning
confidence: 99%
“… 12 , 49 , 63 Sabesan et al found that, compared to other pathologies, use of a reverse shoulder arthroplasty after a proximal humerus fracture was associated with an increased postoperative opioid dependence, and Jildeh et al found specific surgical factors including presence of biceps tenodesis and number of concomitant procedures significantly increased postoperative opioid demand. 39 , 56 Additionally, social and medical history factors including current smoking status, income bracket, young age, history of psychiatric and mood disorders, fibromyalgia, and low back pain have been found to contribute to increased risk. 6 , 18 , 32 , 42 , 43 , 45 , 61 , 66 , 68 Despite significant interest and investigation into individual factors to predict chronic opioid use and dependence, there is a paucity of data in the orthopedic literature on simple, effective screening tools for shoulder surgery patients that are easily implemented in the clinical environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation